Comparison of the First Three Waves of the COVID-19 Pandemic in Russia in 2020–21 - L. S. Karpova; K. A. Stolyarov; N. M. Popovtseva; T. P. Stolyarova; D. M. Danilenko (Эпидемиология и вакцинопрофилактика, 2022)
Relevance. The ongoing COVID-19 pandemic in the world, which is characterized by a long undulating course, requires an in-depth study of the features of the epidemic process, including the influence of natural, climatic and social factors on it. Aim. Compare the intensity of three waves of the COVID-19 pandemic in Russia. To identify the features of the parameters of the COVID-19 pandemic in Russia in the age groups of the population and in the federal districts. Materials and methods. Data from the computer database of the Influenza Research Institute and the Stop-coronavirus website were used. Results. The construction of the weekly dynamics of COVID-19 made it possible to clarify the start, peak and end dates of each wave in megacities, federal districts and among the population of the Russia. Conclusion. In the dynamics of the incidence of COVID-19 in the population of the Russian Federation from March 2020 to September 2021, three waves were detected: I spring-summer wave, II autumn-winter, III spring -summer. All three waves started in megacities, first in Moscow, and spread across federal districts. The rise of morbidity in Russia as a whole began and peaked in the autumn-winter wave later than in the spring-summer waves (immediately after the megacities). The total duration of the epidemic and the period of its development in the autumn-winter wave were longer than in the spring-summer waves. Morbidity, hospitalization and mortality depended on age, and in all three waves were higher among people over 65 years of age. The intensity of COVID-19 in the first spring-summer wave was the lowest. The II autumn-winter wave was the most intense in terms of morbidity, hospitalization rate and mortality in all age groups. The III spring-summer wave in terms of morbidity and hospitalization was less intensive, than the II autumn-winter wave, but there were no significant differences between the mortality rates in the II and III wave hospitalization and fatal outcomes were revealed.